Varón De 21 Años Con Insuficiencia Renal Crónica Y Tratamiento De Diálisis Peritoneal - Menéndez Hurtado, Orlando Xavier (2018)
The present case study is based on a male of 21 years of age, male, university student, lives with his parents, diagnosed three years ago with arterial hypertension, for a year and a half peritoneal dialysis has been performed daily, in a time of 8 hours as a result of chronic renal failure, the patient comes to the nutritional consultation in knowledge of the pathologies presented, his biochemical examination indicated a possible diagnosis of hypernatremia, hypercalcemia, hypercreatinemia, hypoalbuminemia, frequent abdominal pain with 6 days of evolution, accompanied by vomiting after his meals, he thought it was indigestion. The clinical examination reveals a man of normal appearance, heart rate: 125 beats per minute, respiratory rate: 35 breaths per minute, temperature: 36.5 ° C, currently weighs: 75 kilograms, Size: 1.68 meters. Blood pressure 130/90 mmHg. In the anthropometric assessment, the patient started with a BMI: 26.5 Kg / m2. After performing the follow-up and adequate monitoring, we obtained an imc: 24.82 normal, his biochemical values at the beginning were outside the normal ranges, managed to obtain an improvement of it, its clinical aspects reveal that its nutritional status is adequate, its nutritional plan is in accordance with its caloric requirement